Spatial pattern analysis for habitat composition and availability of food sources at Möltenort, Kiel Bight - Friederike Gronwald; Claudia Bommarito; Dakeishla M Díaz-Morales; Alessandro Manfrin; Cindy Martinez Reyes; Milen Nachev; Bernd Sures; Florian Weinberger (PANGAEA, 2025)
The habitat at Möltenort was characterised with a 24 cm x 24 cm metal frame, which was thrown parallel to the coast 30 times within the 100 m transect. Coverage of Amphibalanus spp., Fucus vesiculosus, Gracilaria vermiculophylla, Mytilus spp., sand, stone, Ulva sp., and other ("other" indicating any category not mentioned in the list), was measured in 7 different percentage coverage groups (0, 1-5, 6-10, 11-20, 21-50, 51-75, or 76-100). Measurements were taken in spring, summer and autumn.
In: Gronwald, F et al. (2025): The diet contribution and habitat selection of the common periwinkle Littorina littorea depending on infection with parasites and seasonality [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974526